Changes in the 24 h Rhythmicity of Liver PPARs and Peroxisomal Markers When Feeding Is Restricted to Two Daytime Hours - Julieta B. Rivera-Zavala; Adrián Báez-Ruiz; Mauricio Díaz-Muñoz (PPAR Research)
Restricted feeding (RF) during daytime is associated with anticipatory activity before feeding, marked hyperphagia after mealtime, adjustments in hepatic metabolism, and the expression of a food-entrained oscillator (FEO). 24 h rhythmicity of liver PPARα, β, and γ, peroxisomal markers (PMP70, AOX, and catalase), and free fatty acids (FFAs) during RF was evaluated. The effect of fasting-refeeding was also studied. Results showed (1) higher levels of FFA before feeding, (2) a shift of PPARα and PPARγ before and of PPARβ peaks after feeding, (3) an increase in peroxisomal markers, (4) a shift of PMP70 and AOX peaks before feeding, and of maximal catalase activity in the dark period, (5) changes in the fasting-refeeding response, and (6) high correlations (>0.9) of serum corticosterone with PPARα and PPARγ and of PMP70 with PPARβ. In conclusion, 24 h rhythmicity of FFA, liver PPARs, and peroxisomal markers are biochemical adaptations associated with daytime RF and FEO expression.